Studies on Hispanic diplomatic codices. Historiographic, methodological and systemic confluences in 18th to 20th centuries - Sánchez Díez, Alicia (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
The methodological difficulties of research into Hispanic diplomatic codices, mostly arising from the lack of major systemic treatises, have begun to be resolved to a limited extent in recent years. This is largely due to advanced comparative studies and multidisciplinary methodological systems supported by technological tools, which both allow the diversification of traditional historiographic approaches. This paper sets out an analysis of the confluences and divergences, an examination of developments and improvements in the methodologies used to work on this subject of study over the last three centuries, showing both the influence and effect, not always positive, in current dissertations.